Digitally-Mediated Social Stories Support Children on the Autism Spectrum Adapting to a Change in a ‘Real-World’ Context - Smith, Elizabeth; Constantin, Aurora; Johnson, Hilary; Brosnan, Mark (Journal of autism and developmental disorders, 2021)
Social Stories™ (SS) is a widely used intervention for children on the autism spectrum. A preliminary survey of 103 practitioners highlighted that SS are often used to support adapting to a change. This study investigated the use of digitally-mediated SS to support ten children on the autism spectrum attending a school summer camp. Teacher perceptions of anxiety, understanding and closeness to the goal of the SS were assessed before and after the intervention (prior to the event). The pre- post-intervention comparisons highlighted significant improvements in child understanding, anxiety, and closeness to goal with medium-large effect sizes. The child’s understanding and closeness to SS goal post-intervention related to their difficulties with the SS goal and their anxiety during the event.